Algorithm Optimization for Rockfalls Alarm System Based on Fiber Polarization Sensing - Saverio Pellegrini; Giuseppe Rizzelli; Marco Barla; Roberto Gaudino (IEEE Photonics Journal)
The mountain scenario is often subject to catastrophic events such as rockfalls and avalanches, potentially dangerous for both people and civil infrastructures. Early-warning alarm systems that in case of such events can immediately turn on a traffic light on a mountain road and send remote alarms to control rooms, have already been developed in the geotechnical engineering sector, but all have some limitations and/or very high costs. In this work we propose an immediate-warning monitoring system based on fiber polarization sensing. Anomalies such as rockfalls and avalanches would change the instantaneous birefringence of the fiber installed in the area to be monitored, and can be sensed by looking at the state of polarization at the fiber output. The novelty of our paper is the development of an algorithm that is able to detect dangerous events, which we experimentally emulated on a reduced scale physical model of a mountain slope, in which fibers have been buried in different configurations. Our findings show that the system can correctly sense all the experimentally generated rockfall phenomena and for all the installed fiber configurations, and it is also robust to false alarms, provided that the monitoring algorithm main parameters are properly set.